Optimizing Human Capital with a Strategic Project Office: Select, Train, Measure,and Reward People for Organization Success - Crawford, J. Kent (CRC Press, 2009)
Optimizing Human Capital with a Strategic Project Office explores the SPO's potential to transform an enterprise by making the most of people within an organization. This volume provides an exhaustive review of topics such as the hiring, retention, measurement, training, and professional development of knowledge workers in project management. This book's chapters summarize the latest thinking regarding these issues and offer a model of how the best aspirations of workers can become reality through the medium of the SPO.